2023
DOI: 10.1128/spectrum.01179-22
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus argenteus Infections, Brazil

Abstract: In 2015, two new species related to the Staphylococcus aureus were proposed. We describe five isolates of the new species Staphylococcus argenteus cultured from human cases of bacteremia and skin and soft tissue infections. This is the first report of S. argenteus , from South America, causing community-acquired and nosocomial infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Both ST-2250 and ST-1223 were confirmed as the predominant genotypes in Hong Kong. Additionally, the ST-2250 strain was also identified in other Asian cities, where it caused various forms of infections [6,8,20,21,24]. The ST-1223 is another emerging genotype that has associations with human infections.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both ST-2250 and ST-1223 were confirmed as the predominant genotypes in Hong Kong. Additionally, the ST-2250 strain was also identified in other Asian cities, where it caused various forms of infections [6,8,20,21,24]. The ST-1223 is another emerging genotype that has associations with human infections.…”
Section: Discussionmentioning
confidence: 99%
“…It was later proposed to become a new species in 2015 [4]. An increasing number of cases have been reported in different countries across Oceania, Africa, America, Asia, and Europe between 2015-2023 [5][6][7][8][9][10]. Southeast Asia, the Amazon, and remote regions in Australia have shown a high prevalence of S. argenteus [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3] Subsequently, several studies reported sporadic cases of infections caused by S argenteus in Asia, Oceania, the Pacific Islands, Latin America, Europe, and Africa. [3–6] Here, we describe a fatal case of bacteremia caused by S argenteus isolated from bloodstream of a comatose patient.…”
Section: Introductionmentioning
confidence: 99%